2012
DOI: 10.1007/s11655-012-1211-y
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Baduanjin (八段锦) exercise on knee osteoarthritis: A one-year study

Abstract: It suggested that the long-term Baduanjin could be a feasible and safe exercise option for knee OA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
39
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(40 citation statements)
references
References 23 publications
1
39
0
Order By: Relevance
“…Sample size in the eligible studies ranged from 20 to 222. When compared to Baduanjin Qigong intervention groups, study participants in the control groups were asked to keep either their original lifestyle [9, 13, 17, 18, 20, 32–35], educational lessons relating to diseases [14, 15, 36, 37], regular drug treatment [38, 39], regular healthcare [2, 40], or daily self-walking [11, 41]. Study participants in the Baduanjin Qigong intervention groups (intervention period ranging from 4 to 24 weeks) experienced Baduanjin Qigong exercise duration ranging from 30 to 90 minutes, along with the frequency of weekly sessions from 2 to 7.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Sample size in the eligible studies ranged from 20 to 222. When compared to Baduanjin Qigong intervention groups, study participants in the control groups were asked to keep either their original lifestyle [9, 13, 17, 18, 20, 32–35], educational lessons relating to diseases [14, 15, 36, 37], regular drug treatment [38, 39], regular healthcare [2, 40], or daily self-walking [11, 41]. Study participants in the Baduanjin Qigong intervention groups (intervention period ranging from 4 to 24 weeks) experienced Baduanjin Qigong exercise duration ranging from 30 to 90 minutes, along with the frequency of weekly sessions from 2 to 7.…”
Section: Resultsmentioning
confidence: 99%
“…Concealed allocation, blinding of participants, and blinding of therapists were not observed in all RCTs, which is acceptable because of nonpharmacological clinical trials [4244]. Blinding of assessors was present in 12 RCTs [9, 11, 1315, 20, 32, 35–37, 40, 41] but not employed in 7 RCTs [2, 17, 18, 33, 34, 38, 39]. Of 19 RCTs, only four RCTs were observed that the dropout rate was greater than 15% [2, 20, 32, 36].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Unlike Tai Chi, Baduanjin exercise is characterized by simple, slow, relaxing movements, which is composed of 8 set of actions including support heaven with both hands, dragon sprays water with force, big bird spreads its wings, lift window to look at the moon on the left, descend to earth with force, beautiful maiden twists her waist to the right, extend shoulders to bring hands together, and dragon claws to the left [9]. In China, it has been widely practiced for the treatment of various conditions, including hyperlipidemia [12], ischemic stroke [13], sleep disturbances [14], knee osteoarthritis [15], bone loss [16], and oxidative stress [17], due to its promotion of good health [18], ease of learning, low physical demand [19], and gentle nature compared to intense exercise [20]. Furthermore, the Chinese Health Qigong Association recommends Baduanjin for generalized application in the community.…”
Section: Introductionmentioning
confidence: 99%
“…The slow, gentle, graceful movements of Ba Duan Jin, combined with meditation, deep breathing, and relaxation, move Qi throughout the body. Current studies have suggested that Ba Duan Jin training appears to have substantive benefits for older adults with physical and mental disorders, such as anxiety, depression, hyperlipidemia, spinal problems, osteoarthrosis, and type 2 diabetes (An et al, 2013;Hsu, Wang, Liu, & Liu, 2008;Mei, Chen, Ge, Zheng, & Chen, 2012). Ba Duan Jin has several health effects, and the levels of exercise intensity and simplicity of movements make it suitable for practice among older adults.…”
mentioning
confidence: 99%